La expresión artística y su incidencia en el desarrollo psicomotriz de los niños y niñas de primer año de educación general básica del jardín de infantes “Eloy Alfaro” de la parroquia Lizarzaburu de la ciudad de Riobamba durante el año lectivo 2013 – 2014 - Peralta Granizo, Rosario del Pilar (2014)
This work refers to the study on "The Artistic Expression and their impact in Psychomotor Develpment Children‟s from First Year of Basic General Education of "Eloy Alfaro" kindergarten from Riobamba city Lizarzaburu parish during the school year 2013-2014", being structured and developed in accordance to the regulation of graduation in term of the Loja National University. Arose the following overall objective: Educate the teachers about the Artistic Expression Importance in the Children‟s psychomotor development of the First Year of Basic General Education of "Eloy Alfaro" kindergarten of parish Lizarzaburu from the Riobamba city in the 2013-2014 school year. In the methodological part are used the following methods: Scientist, Inductive, Deductive, Descriptive and Statistical model. Techniques applied were the survey, directed to kindergartens teachers of children‟s First Year of Basic General Education of "Eloy Alfaro" kindergarten from the Riobamba city parish Lizarzaburu to know the use of ArtisticExpression in the daily workday; Observation Guide applied to children for results on the psychomotor development and, the Denver Test which was applied to children‟s from First Grade of Basic General Education in "Eloy Alfaro" kindergarten from the Riobamba city parish Lizarzaburu, to evaluate the Psychomotor Development. With the data obtained in the survey analysis it is concluded that 100% of the teachers is in agreement that the Psychomotor Development of children is influenced positively by means of different forms of Artistic Expression, consists in planning for the day activities related to 29% of those Artistic Expression constitutes music, another 29% literature, 28 per cent the technical plastic graph, followed by the dance with a 14%. With Observation Guide analysis it is concluded that the 92% of the observed averages activities very satisfactory, and 8% performed activities with an average satisfactory, where we can see that there are no major problems with the Psychomotor Development, and it also reveals that Artistic Expression, positively affect the Children‟s Psychomotor Development. In applying the Test of Denver can notice 95% has a Normal Psychomotor Development, while 5% reveals that he has a Normal Psychomotor Development, showing that the information revealed by the Observation Guide and the Test of Denver agree on the results of the Children‟s Psychomotor Development.